Peran Sektor Pertanian dalam Meningkatkan Kemajuan Pertumbuhan Ekonomi di Wilayah Kabupaten Lampung Barat - Tia Hidayah; Pani Emilia Amanda; Anggun Dwi A; M.Yusuf Bahtiar (Universitas 45 Surabaya, 2026)
The agricultural sector remains the backbone of economic sustainability in rural areas of Indonesia. This research aims to explore in depth the role of the agricultural sector in promoting the advancement of rural economic growth through a descriptive qualitative approach. Data were collected through literature studies, field observations, and analysis of documents related to rural development policies. The main focus of this research is to identify how the interaction between the availability of natural resources, local wisdom, and government policies creates economic stability at the village level. The results show that the role of the agricultural sector is not only limited to fulfilling food needs but also serves as the main provider of employment, which helps prevent excessive urbanization.It was found that strengthening farmer group institutions and improving access to market information are key factors in enhancing the economic competitiveness of rural areas. In addition, agricultural technology innovation and the improvement of human resource quality also play an important role in supporting productivity.This study concludes that the transformation from traditional agriculture to value-added agriculture is highly necessary to accelerate rural economic progress. The recommendation of this research is the need for synergy between village governments and the private sector in creating a more modern and independent agricultural ecosystem that is innovative for the welfare of rural communities.